Liquid electrolyte, and rechargeable lithium battery including the same
Patent Information
- Application Number
- KR1020230100657
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2043-08-01
Smart Images

Figure 112023084945380-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a liquid electrolyte and a lithium secondary battery containing the same. Background Technology
[0002] Lithium secondary batteries are rechargeable and have an energy density more than three times higher per unit weight than conventional lead-acid batteries, nickel-cadmium batteries, nickel-hydrogen batteries, and nickel-zinc batteries, and can be fast-charged. As a result, they are being commercialized for laptops, mobile phones, power tools, and electric bicycles, and research and development to further improve energy density is actively underway.
[0003] These lithium secondary batteries are used by injecting an electrolyte into a battery cell comprising a positive electrode containing a positive electrode active material capable of intercalating and deintercalating lithium, and a negative electrode containing a negative electrode active material capable of intercalating and deintercalating lithium.
[0004] Currently, the electrolytes of commercially available lithium secondary batteries use organic carbonate-based solvents to withstand high operating voltages.
[0005] However, organic carbonate-based solvents have high volatility and flammability, and their low flash points can cause the battery to swell due to vaporization at high temperatures and the polyethylene (PE) separator to melt and shrink, potentially leading to safety issues in lithium-ion batteries.
[0006] Despite extensive research involving separators, current collectors, active materials, and Battery Management Systems (BMS) being conducted to address the safety issues of lithium-ion batteries, resolving these problems remains difficult as long as highly flammable organic solvents are used. In fact, with the recent frequent occurrence of fire incidents in electric vehicles, the safety of lithium-ion batteries is being actively discussed; in particular, solutions must be derived from the perspective of electrolytes to fundamentally resolve these issues. The problem to be solved
[0007] One embodiment provides a liquid electrolyte capable of achieving excellent battery safety.
[0008] Another embodiment provides a lithium secondary battery comprising the above-mentioned liquid electrolyte. means of solving the problem
[0009] One embodiment of the present invention provides a liquid electrolyte comprising a lithium salt; a non-aqueous organic solvent; and an additive, wherein the additive comprises a polymer represented by the following chemical formula 1.
[0010] [Chemical Formula 1]
[0011]
[0012] In the above chemical formula 1,
[0013] R 1 to R 3 Each is independently hydrogen, fluorine, or a substituted or unsubstituted C1 to C10 alkyl group, and
[0014] n and m are mole fractions, respectively, 50 mol%≤n≤90 mol% and 10 mol%≤m≤50 mol%.
[0015] Another embodiment of the present invention provides a lithium secondary battery comprising a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and the above-described liquid electrolyte. Effects of the invention
[0016] We provide a lithium secondary battery with improved safety that can prevent short circuits, overheating, and explosions by blocking ion conduction in the event of an issue, suppressing swelling caused by the vaporization of the electrolyte, and suppressing the shrinkage of the separator. Brief explanation of the drawing
[0017] FIGS. 1 to 4 are cross-sectional views schematically illustrating a lithium secondary battery according to one embodiment. Figure 5 is a graph showing the discharge capacity and Coulomb efficiency according to the progress of the high-temperature charge / discharge cycle for a lithium secondary battery. Figure 6 is a result graph showing the results of the hot-box test of the pouch full cell. Figure 7 is a graph showing the TGA analysis results of a liquid electrolyte according to one embodiment of the present invention. Figure 8 shows the results of measuring the DC resistance of a cell maintained for 1 hour after reaching room temperature (25℃) and high temperature (120℃). Specific details for implementing the invention
[0018] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.
[0019] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. Singular expressions include plural expressions unless the context clearly indicates otherwise.
[0020] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.
[0021] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0022] Unless otherwise defined in this specification, the particle size may be the average particle size. Additionally, the particle size refers to the average particle size (D50), which means the diameter of the particle whose cumulative volume in the particle size distribution is 50% by volume. The average particle size (D50) may be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with a transmission electron microscope (TEM) image or a scanning electron microscope (SEM) image. Alternatively, the average particle size (D50) value may be obtained by measuring using a measuring device utilizing dynamic light scattering, performing data analysis to count the number of particles for each particle size range, and then calculating from this. Alternatively, it may be measured using a laser diffraction method. When measuring by laser diffraction, more specifically, after dispersing the particles to be measured in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasound of about 28 kHz at an output of 60 W, and then the average particle size (D50) at 50% of the particle size distribution in the measuring device can be calculated.
[0023] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.
[0024] In addition, the term “layer” here includes not only shapes formed on the entire surface when viewed in a plan view, but also shapes formed on some surfaces.
[0025] Here, “or” is not interpreted in an exclusive sense; for example, “A or B” is interpreted to include A, B, A+B, etc.
[0026] The term “metal” is interpreted as a concept that includes ordinary metals, transition metals, and metalloids (semimetals).
[0027] In this specification, "substitution" means that, unless otherwise defined, at least one hydrogen of a substituent or compound is substituted with a deuterium, a halogen group, a hydroxyl group, an amino group, a substituted or unsubstituted C1 to C30 amine group, a nitro group, a substituted or unsubstituted C1 to C40 silyl group, a C1 to C30 alkyl group, a C1 to C10 alkylsilyl group, a C6 to C30 arylsilyl group, a C3 to C30 cycloalkyl group, a C3 to C30 heterocycloalkyl group, a C6 to C30 aryl group, a C2 to C30 heteroaryl group, a C1 to C20 alkoxy group, a C1 to C10 fluoroalkyl group, a cyano group, or a combination thereof.
[0028] In one example of the present invention, "substitution" means that at least one hydrogen in a substituent or compound is substituted with deuterium, a halogen group, a C1 to C30 alkyl group, a C1 to C10 alkylsilyl group, a C6 to C30 arylsilyl group, a C3 to C30 cycloalkyl group, a C3 to C30 heterocycloalkyl group, a C6 to C30 aryl group, a C2 to C30 heteroaryl group, a C1 to C10 fluoroalkyl group, or a cyano group. Furthermore, in a specific example of the present invention, "substitution" means that at least one hydrogen in a substituent or compound is substituted with deuterium, a halogen group, a C1 to C20 alkyl group, a C6 to C30 aryl group, a C1 to C10 fluoroalkyl group, or a cyano group. In addition, in a specific example of the present invention, "substitution" means that at least one hydrogen in the substituent or compound is substituted with deuterium, a halogen group, a C1 to C5 alkyl group, a C6 to C18 aryl group, a C1 to C5 fluoroalkyl group, or a cyano group. In addition, in a specific example of the present invention, "substitution" means that at least one hydrogen in the substituent or compound is substituted with deuterium, a cyano group, a halogen group, a methyl group, an ethyl group, a propyl group, a butyl group, a phenyl group, a biphenyl group, a terphenyl group, a trifluoromethyl group, or a naphthyl group.
[0029] Lithium secondary batteries can be classified into cylindrical, prismatic, pouch, coin, etc., depending on their shape. FIGS. 1 to 4 are schematic diagrams illustrating a lithium secondary battery according to one embodiment, where FIG. 1 is a cylindrical battery, FIG. 2 is a prismatic battery, and FIGS. 3 and 4 are pouch-type batteries. Referring to FIGS. 1 to 4, the lithium secondary battery (100) may include an electrode assembly (40) having a separator (30) interposed between a positive electrode (10) and a negative electrode (20), and a case (50) in which the electrode assembly (40) is housed. The positive electrode (10), the negative electrode (20), and the separator (30) may be impregnated with an electrolyte (not shown). The lithium secondary battery (100) may include a sealing member (60) that seals the case (50) as in FIG. 1. In addition, in FIG. 2, the lithium secondary battery (100) may include a positive lead tab (11) and a positive terminal (12), a negative lead tab (21) and a negative terminal (22). As shown in FIG. 3 and FIG. 4, the lithium secondary battery (100) may include an electrode tab (70), namely a positive tab (71) and a negative tab (72), which serve as an electrical path to guide the current formed in the electrode assembly (40) to the outside.
[0030] Hereinafter, an electrolyte according to one embodiment is described.
[0031] An electrolyte according to one embodiment of the present invention is a liquid electrolyte and comprises a lithium salt, a non-aqueous organic solvent, and an additive, wherein the additive may comprise a polymer represented by the following chemical formula 1.
[0032] [Chemical Formula 1]
[0033]
[0034] In the above chemical formula 1,
[0035] R 1 to R 3 Each is independently hydrogen, fluorine, or a substituted or unsubstituted C1 to C10 alkyl group, and
[0036] n and m are mole fractions, respectively, 50 mol%≤n≤90 mol% and 10 mol%≤m≤50 mol%.
[0037] The polymer represented by Chemical Formula 1 above gels by crystallization within the liquid electrolyte upon exposure to high temperatures of 100°C or higher, thereby not only suppressing the vaporization of the electrolyte and the resulting expansion of the battery, but also blocking the ion and electron conduction of the battery, and approximately 140 By physically fixing the PE separator that melts and shrinks at ℃, the rapid release of energy caused by direct contact between the anode and cathode, i.e., a short circuit, can be prevented, thereby suppressing fire and explosion caused by this and improving the safety of the battery.
[0038] In particular, the polymer represented by the above chemical formula 1 is dispersed within the liquid electrolyte before issues such as high temperature or shock occur, and since the electrolyte containing the polymer represented by the above chemical formula 1 is a liquid electrolyte, the composition of the phase of the electrolyte is different from that of the solid electrolyte formed by polymerizing the polymer together with the polymerization initiator.
[0039] In the case of a solid electrolyte, since the electrolyte exists in a solid state within the battery, the ionic conductivity is low, resulting in low output and a short lifespan; therefore, there will be a significant difference in effectiveness compared to a battery using a liquid electrolyte according to the present invention.
[0040] For example, the above n and m may be 80 mol% : 20 mol% to 60 mol% : 40 mol% or 80 mol% : 20 mol% to 70 mol% : 30 mol%.
[0041] The higher the content of vinylidene fluoride structural units in the polymer relative to the content of trifluoroethylene structural units, the more effectively the improvement in battery stability can be observed.
[0042] The molecular weight of the above polymer may be 100,000 g / mol to 400,000 g / mol.
[0043] For example, the molecular weight of the above polymer may be 200,000 g / mol to 400,000 g / mol.
[0044] The above polymer may be in the form of particles having an average particle size of 10 nm to 1 µm.
[0045] For example, the average particle size of the above polymer may be 10 nm to 900 nm, 10 nm to 800 nm, 10 nm to 700 nm, or 10 nm to 600 nm.
[0046] For example, the average particle size of the above polymer may be 30 nm to 1 µm, 50 nm to 1 µm, 100 nm to 1 µm, 100 nm to 900 nm, 100 nm to 800 nm, 100 nm to 700 nm, or 100 nm to 600 nm.
[0047] The polymer may be in particulate form, and if the average particle size is within the above range, the precipitation of the polymer in the electrolyte may be mitigated, thereby mitigating the capacity degradation due to repeated cycles.
[0048] As an example, R of the above chemical formula 1 1 to R 3 Each can independently be hydrogen, or a substituted or unsubstituted C1 to C5 alkyl group.
[0049] For example, the above polymer may be poly(vinylidene fluoride-co-trifluoroethylene).
[0050] The above polymer can be gelled at a temperature of 100°C to 120°C.
[0051] For example, the above polymer may be included in an amount of 0.1 to 15 parts by weight per 100 parts by weight of the total liquid electrolyte.
[0052] Specifically, the polymer may be included in an amount of 0.5 to 15 parts by weight, for example, 1 to 15 parts by weight, or 5 to 15 parts by weight, based on 100 parts by weight of the total liquid electrolyte.
[0053] When the polymer content range is as described above, it is possible to realize a lithium secondary battery with improved stability by preventing an increase in resistance at high temperatures while securing lifespan and output characteristics.
[0054] The above-mentioned non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0055] The above-mentioned non-aqueous organic solvent may be a carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvent.
[0056] The above carbonate-based solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. The above ester-based solvents may include methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methylpropionate, ethylpropionate, propylpropionate, decanolide, mevalonolactone, caprolactone, etc. The above ether-based solvents may include dibutyl ether, tetraglame, deglame, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc. In addition, cyclohexanone, etc. may be used as the ketone-based solvent. Furthermore, ethyl alcohol, isopropyl alcohol, etc. may be used as the alcohol-based solvent, and R may be used as the aprotic solvent. 1 -CN(R 1Nitriles such as dimethylformamide, amides such as dioxolanes such as 1,3-dioxolane, sulfolanes, etc., may be used. (It is a hydrocarbon group with a straight, branched, or ring structure having 2 to 20 carbon atoms and may include a double bond direction ring or ether bond.)
[0057] The above-mentioned non-aqueous organic solvents may be used alone or in a mixture of one or more. When used in a mixture of one or more, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.
[0058] A non-aqueous organic solvent according to one embodiment of the present invention may contain cyclic carbonates and linear carbonates in a volume ratio of 10:90 vol% to 50:50 vol%.
[0059] Specifically, the above-mentioned non-aqueous organic solvent may contain cyclic carbonates and linear carbonates in a volume ratio of 10:90 vol% to 40:60 vol%, for example, a volume ratio of 10:90 vol% to 30:70 vol% or a volume ratio of 10:90 vol% to 25:75 vol%.
[0060] In the non-aqueous organic solvent of the aforementioned composition, as the polymer in the liquid electrolyte gels above a certain temperature, the viscosity of the electrolyte increases and the resistance increases. Consequently, the gelled polymer acts as an insulator, blocking the ion and electron conduction of the battery, thereby ensuring the stability of the battery.
[0061] The above liquid electrolyte may further include at least one other additive selected from vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinonitrile (SN), 1,3,6-hexane tricyanide (HTCN), propensulfone (PST), propanesulfone (PS), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), and 2-fluorobiphenyl (2-FBP).
[0062] By further including the aforementioned other additives, the lifespan can be further improved, or gases generated at the anode and cathode during high-temperature storage can be effectively controlled.
[0063] The above other additives may be included in an amount of 0.2 to 20 parts by weight per 100 parts by weight of the total electrolyte for the lithium secondary battery, and specifically, may be included in an amount of 0.2 to 15 parts by weight, for example, 0.2 to 10 parts by weight.
[0064] When the content of other additives is as described above, the increase in film resistance can be minimized, thereby contributing to the improvement of battery performance.
[0065] The above lithium salt is a substance that dissolves in an organic solvent and acts as a source of lithium ions within the battery, enabling the basic operation of a lithium secondary battery and facilitating the movement of lithium ions between the anode and cathode. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide (LiFSI), LiC4F9SO3, LiN(C x F 2x+1SO2)(C y F 2y+1 It may include one or more selected from SO2)(x and y are integers from 1 to 20), lithium trifluoromethane sulfonate, lithium tetrafluoroethane sulfonate, lithium difluorobis(oxalate)phosphate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).
[0066] Another embodiment of the present invention provides a lithium secondary battery comprising a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; and the above-described liquid electrolyte.
[0067] The above positive electrode comprises a positive current collector and a positive active material layer located on the positive current collector, wherein the positive active material layer comprises a positive active material and optionally further comprises a binder and / or a conductive material.
[0068] As a positive electrode active material, a compound capable of reversible intercalation and deintercalation of lithium (a lithated intercalation compound) may be used. Specifically, one or more composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof may be used.
[0069] The above composite oxide may be a lithium transition metal composite oxide, and specific examples include a lithium nickel-based oxide, a lithium cobalt-based oxide, a lithium manganese-based oxide, a lithium iron phosphate-based compound, a cobalt-free nickel-manganese-based oxide, or a combination thereof.
[0070] As an example, a compound represented by any one of the following chemical formulas may be used. Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c About 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b-c Mn b X c About 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NiG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3(0≤f≤2); Li a FePO4(0.90≤a≤1.8).
[0071] In the above chemical formula, A is Ni, Co, Mn, or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; L 1 is Mn, Al, or a combination thereof.
[0072] For example, the above-mentioned positive electrode active material may be a high-nickel positive electrode active material in which the nickel content relative to 100 mol% of the metal excluding lithium in the lithium transition metal composite oxide is 80 mol% or more, 85 mol% or more, 90 mol% or more, 91 mol% or more, or 94 mol% or more and 99 mol% or less. The high-nickel positive electrode active material can achieve high capacity and can be applied to high-capacity, high-density lithium secondary batteries.
[0073] The content of the positive active material is 90% to 99.9% by weight with respect to 100% by weight of the positive active material layer, and the content of the binder and the conductive material may each be 0.1% to 5% by weight with respect to 100% by weight of the positive active material layer.
[0074] The above binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the positive current collector. Representative examples of binders include, but are not limited to, polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0075] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube; metal-based materials in the form of metal powder or metal fibers containing copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0076] Al may be used as the anode current collector, but is not limited thereto.
[0077] The above cathode comprises a cathode current collector and a cathode active material layer located on the cathode current collector, and the cathode active material layer comprises a cathode active material and may optionally further comprise a binder and / or a conductive material.
[0078] The above-mentioned negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0079] A material capable of reversibly intercalating / deintercalating the above lithium ions may be a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0080] As the above lithium metal alloy, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0081] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiOx (0 < x < 2), a Si-Q alloy (wherein Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn-based alloy, or a combination thereof.
[0082] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to one embodiment, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, it may include a secondary particle (core) assembled from silicon primary particles and an amorphous carbon coating layer (shell) located on the surface of the secondary particle. The amorphous carbon may also be located between the silicon primary particles, so that, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0083] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core comprising crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core.
[0084] The above Si-based or Sn-based negative electrode active material can be used in combination with a carbon-based negative electrode active material.
[0085] For example, the negative electrode active material layer may comprise 90% to 99% by weight of negative electrode active material, 0.5% to 5% by weight of binder, and 0% to 5% by weight of conductive material.
[0086] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof may be used.
[0087] Examples of the above-mentioned non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide imide, polyimide, or combinations thereof.
[0088] The above-mentioned water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0089] When a water-based binder is used as the above-mentioned cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal.
[0090] The above dry binder is a polymer material capable of fiberization, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0091] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjenblack, carbon fiber, carbon nanofiber, carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0092] As the above-mentioned cathode current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof may be used.
[0093] Depending on the type of lithium secondary battery, a separator may be present between the positive and negative electrodes. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or multilayer films of two or more layers thereof may be used, and of course, mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators may be used.
[0094] The above separator may include a porous substrate and a coating layer comprising an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0095] The porous substrate may be a polymer membrane formed from any one of the following: polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyacetal; polyamide; polyimide; polycarbonate; polyetherketone; polyaryletherketone; polyetherimide; polyamideimide; polybenzimidazole; polyethersulfone; polyphenylene oxide; cyclic olefin copolymer; polyphenylene sulfide; polyethylene naphthalate; glass fiber; Teflon; and polytetrafluoroethylene, or a copolymer or mixture of two or more of these.
[0096] The above organic material may include a polyvinylidene fluoride-based antibody or a (meth)acrylic-based polymer.
[0097] The above inorganic materials are Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, It may include, but is not limited to, inorganic particles selected from SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof.
[0098] The above organic and inorganic materials may exist mixed in a single coating layer, or may exist in a stacked form with a coating layer containing organic materials and a coating layer containing inorganic materials.
[0100] Examples and comparative examples of the present invention are described below. The following examples are merely embodiments of the present invention, and the present invention is not limited to the following examples.
[0101] (Example: Fabrication of a lithium secondary battery)
[0102] Example 1
[0103] LiNi as a positive electrode active material 0.8 Co 0.1 Mn 0.1O2, polyvinylidene fluoride as a binder, and acetylene black as a conductive material are mixed in a weight ratio of 97.5:1:1.5, respectively. N - A positive electrode active material slurry was prepared by dispersing in methylpyrrolidone.
[0104] The above positive active material slurry was coated onto an Al foil with a thickness of 15 μm, dried at 100°C, and then pressed to produce a positive electrode.
[0105] Artificial graphite was used as the cathode active material, and the cathode active material, styrene-butadiene rubber binder, and carboxymethylcellulose were mixed in a weight ratio of 98:1:1, respectively, and dispersed in distilled water to prepare a cathode active material slurry.
[0106] The above cathode active material slurry was coated onto a 10㎛ thick Cu foil, dried at 100℃, and then pressed to manufacture a cathode.
[0107] An electrode assembly was manufactured by assembling the above-manufactured positive and negative electrodes with a polyethylene separator with a thickness of 10 μm, and a lithium secondary battery was manufactured by injecting the following liquid electrolyte.
[0108] The composition of the liquid electrolyte is as follows.
[0109] (Liquid electrolyte composition)
[0110] Lithium salt: LiPF6 1.15 M
[0111] Non-aqueous organic solvent: Ethylene carbonate: Ethylmethyl carbonate: Dimethyl carbonate (volume ratio of EC:EMC:DMC = 20:40:40)
[0112] Additives:
[0113] (1) Polymer: 15 parts by weight of Solvene®200 / P200 (Mw=200,000, n:m=80:20; Solvay),
[0114] (2) 1 part by weight of vinylene carbonate (VC)
[0115] (However, in the above electrolyte composition, “parts by weight” refers to the relative weight of the additive to the total weight of the electrolyte (lithium salt + non-aqueous organic solvent) excluding the additive.)
[0116] Example 2
[0117] A lithium secondary battery was manufactured in the same manner as in Example 1 above, except that Solvene®200 / P400 (Mw=400,000, n:m=80:20; Solvay) was used instead of Solvene®200 / P200.
[0118] Example 3
[0119] A lithium secondary battery was manufactured in the same manner as in Example 1 above, except that Solvene®250 / P400 (Mw=400,000, n:m=75:25; Solvay) was used instead of Solvene®200 / P200.
[0120] Examples 4 and 5
[0121] A lithium secondary battery was manufactured using the same method as in Example 1, except that the liquid electrolyte was prepared by changing the content of the above polymer to 5 parts by weight and 10 parts by weight, respectively.
[0122] Comparative Example 1
[0123] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the above polymer was not used.
[0124] Comparative Example 2
[0125] In 95.5 g of a non-aqueous organic solvent (volume ratio of ethylene carbonate:ethylmethyl carbonate:dimethyl carbonate = 20:40:40) in which 1.15 M LiPF6 and 1 part by weight of vinylene carbonate (VC) are dissolved A lithium secondary battery was prepared in the same manner as in Example 1, except that a composition comprising 1 g of polymer (Solvene®200 / P200) and 0.5 g of polymerization initiator (AIBN) was added and heated at 60°C for 24 hours to form a gel polymer electrolyte.
[0127] Evaluation 1: High Temperature (45℃) Life Characteristics Evaluation
[0128] For the lithium secondary batteries prepared in Examples 1, 4, 5 and Comparative Example 1, charging and discharging were performed at 1C for 3 cycles, and then 50 cycles were carried out by continuously charging at 1.5C and discharging at 1C to evaluate the discharge capacity and Coulomb efficiency of the batteries, and the results are shown in FIG. 5. The voltage range used at this time was 3.0V to 4.2V (discharging up to 3.0V and charging up to 4.2V), and the evaluation temperature was 45℃.
[0129] Figure 5 is a graph showing the discharge capacity and Coulomb efficiency according to the progress of the high-temperature charge / discharge cycle for a lithium secondary battery.
[0130] Referring to FIG. 5, it can be seen that the discharge capacity and Coulomb efficiency of the liquid electrolyte containing the polymer according to the present invention are maintained at an equivalent or higher level compared to the liquid electrolyte not containing the polymer. From this, it can be predicted that the lifespan characteristics of the battery will not deteriorate and will be maintained at an excellent level.
[0132] Review 2: Hotbox Review
[0133] Figure 6 shows the results of comparing the degree of volume expansion of pouch full cells according to Examples 1 to 5 and Comparative Example 1 after charging to SOC 50 (3.94V) following a formation cycle and then exposing them to silicone oil at 130°C for 5 minutes.
[0134] Figure 6 is a result graph showing the results of the hot-box test of the pouch full cell.
[0135] Referring to Fig. 6, in the case of a pouch cell without a polymer (Comparative Example 1), the pouch cell burst due to volume expansion caused by the gasification of the electrolyte, whereas in the case of a pouch cell containing a polymer (Example), the degree of volume expansion was mitigated as the gasification of the electrolyte was suppressed. In other words, it can be seen that thermal safety is improved even in high-temperature storage environments when a liquid electrolyte containing a polymer is included.
[0137] Evaluation 3: TGA (Thermogravimetric analysis) evaluation
[0138] TGA analysis was performed on Example 1, Comparative Examples 1 and 2 to measure the change in weight of the material according to the change in temperature, and the results are shown in Fig. 7.
[0139] Figure 7 is a graph showing the TGA analysis results of a liquid electrolyte according to one embodiment of the present invention.
[0140] Referring to Fig. 7, for the liquid electrolyte according to Example 1, the TGA analysis results show that the temperature at which the mass at room temperature is halved due to vaporization and thermal decomposition is 124 o At C, the temperature at which the mass of the liquid electrolyte (polymer-free) according to Comparative Example 1 is halved (82 o C) Compared to 42 o It can be seen that C has increased. This indicates that when a liquid electrolyte containing a dissolved polymer is introduced, the organic solvent participates in the dissolution of the polymer, causing a boiling point elevation due to van der Waals forces between the polymer and the solvent. Consequently, the vaporization of the electrolyte at high temperatures is delayed, which can delay the explosion caused by the expansion of the battery and the increase in internal pressure.
[0141] Meanwhile, when evaluated as a polymer itself, no mass reduction occurs, and from this, it was confirmed that in the case of Comparative Example 2, to which a gel polymer electrolyte is applied, the effects of delaying the vaporization of the electrolyte, battery expansion, and delaying explosion due to increased internal pressure, which are the objectives of the present invention, cannot be expected.
[0143] Evaluation 4: High-temperature DC resistance (DC-IR) characteristic evaluation
[0144] For the lithium secondary battery prepared according to Example 1 and Comparative Example 1, the initial DC resistance (DCIR) was measured using the △V / △I (change in voltage / change in current) value, the maximum energy state inside the battery was made to a fully charged state (SOC 100%), the DC resistance at room temperature (25℃) was measured in this state, and the DC resistance of the cell was measured after reaching a high temperature (120℃) and maintaining it for 1 hour, and the results are shown in FIG. 8.
[0145] Figure 8 shows the results of measuring the DC resistance of a cell maintained for 1 hour after reaching room temperature (25℃) and high temperature (120℃).
[0146] Referring to FIG. 8, it can be anticipated that the battery incorporating the liquid electrolyte according to Example 1 will have its resistance significantly increased due to gelation of the electrolyte when the temperature rises to 120°C, and accordingly, the gelled electrolyte will act as an insulator between the positive and negative electrodes, thereby reducing the risk of rapid energy release, explosion, and fire caused by a short circuit between the positive and negative electrodes.
[0148] Evaluation 5: Evaluation of DC Resistance (DC-IR) Characteristics After High Temperature Storage
[0149] For the lithium secondary batteries prepared according to Example 1 and Comparative Example 2, the initial DC internal resistance (DC-IR) was measured using the △V / △I (change in voltage / change in current) value, the maximum energy state inside the battery was made to a fully charged state (SOC 100%), the DC internal resistance at a high temperature (25℃) was measured in this state, and the DC internal resistance after being left at a high temperature (60℃) for 5 days was measured, and the results are shown in Table 3.
[0150] Initial DC internal resistance (Ω) DC internal resistance (Ω) after being left at 60℃ for 5 days Growth rate (%) Example 1 12.1 14.2 17.4 Comparative Example 2 13.5 27.5 103.7
[0151] Referring to Table 3, it can be seen that when the gel polymer is formed (Comparative Example 2), an increase in resistance already occurs at 50°C to 60°C where the initiator operates, and the high-temperature storage resistance value of the cell is higher than that of the example. In addition, an additional increase in resistance occurs due to the resistance increase caused by the continuous cross-linking reaction, and consequently, the rate of increase in resistance is very high compared to the example.
[0152] On the other hand, since the polymer in the liquid electrolyte according to the example gels at a temperature of 100°C to 120°C, there is almost no increase in resistance due to gelation at 60°C, so the resistance at 60°C is confirmed to be relatively low.
[0154] From this, the liquid electrolyte containing the polymer additive according to the present invention undergoes gelation as the polymer crystallizes at high temperatures, and the gelled liquid electrolyte forms a solid film and acts as an insulator, thereby blocking ion conduction and electrical conduction between the anode and the cathode, so that ignition or explosion of the battery can be suppressed.
[0155] In addition, the gelled liquid electrolyte can suppress high-temperature shrinkage of the separator by physically bonding the anode, separator, and cathode, thereby preventing short circuits between the anode and cathode.
[0157] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto and can be implemented with various modifications within the scope of the claims, the detailed description of the invention, and the attached drawings, and it is obvious that such modifications also fall within the scope of the present invention. Explanation of the symbols
[0158] 100: Lithium secondary battery 10: Positive electrode 11: Positive lead tab 12: Positive terminal 20: Cathode 21: Cathode lead tab 22: Negative terminal 30: Separator 40: Electrode assembly 50: Case 60: Sealing member 70: Electrode tab 71: Positive tab 72: Negative tab
Claims
Claim 1 A liquid electrolyte comprising a lithium salt; a non-aqueous organic solvent; and an additive, wherein the additive comprises a polymer represented by the following chemical formula 1 and vinylene carbonate (VC): [Chemical Formula 1] In the above chemical formula 1, R 1 to R 3 Each is independently hydrogen, fluorine, or a substituted or unsubstituted C1 to C10 alkyl group, and n and m are each mole fractions, 50 mol%≤n≤90 mol%, 10 mol%≤m≤50 mol%. Claim 2 In claim 1, the liquid electrolyte, wherein n and m are 80 mol% : 20 mol% to 60 mol% : 40 mol%. Claim 3 A liquid electrolyte according to claim 1, wherein the weight-average molecular weight (Mw) of the polymer is 100,000 g / mol to 400,000 g / mol. Claim 4 In claim 1, the polymer is a liquid electrolyte in the form of particles having an average particle size of 10 nm to 1 μm. Claim 5 In claim 1, R of the above chemical formula 1 1 to R 3 A liquid electrolyte, each independently hydrogen, or a substituted or unsubstituted C1 to C5 alkyl group. Claim 6 In claim 1, the polymer is a liquid electrolyte, which is poly(vinylidene fluoride-co-trifluoroethylene). Claim 7 In claim 1, the liquid electrolyte is such that the polymer gels at a temperature of 100°C to 120°C. Claim 8 A liquid electrolyte according to claim 1, wherein the polymer is included in an amount of 0.1 to 15 parts by weight per 100 parts by weight of the total liquid electrolyte. Claim 9 In claim 1, the liquid electrolyte comprises a cyclic carbonate and a linear carbonate in a volume ratio of 10:90 vol% to 50:50 vol%. Claim 10 An electrolyte for a lithium secondary battery according to claim 1, wherein the liquid electrolyte further comprises at least one other additive selected from fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinonitrile (SN), 1,3,6-hexane tricyanide (HTCN), propenesulfone (PST), propanesulfone (PS), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), and 2-fluorobiphenyl (2-FBP). Claim 11 A lithium secondary battery comprising: a positive electrode including a positive active material; a negative electrode including a negative active material; and a liquid electrolyte according to any one of claims 1 to 10.
Citation Information
Patent Citations
Solid polymer electrolyte and preparation method and application thereof
CN114678589A
Polymer electrolyte sheet and manufacturing method thereof, and electrochemical device and manufacturing method thereof
JP2020053229A
Secondary battery
JP2000182668A
Gel Electrolyte and Gel Electrolyte Cell
KR1020010030538A
Resin dispersion electrolyte, polymer gel electrolyte and method for producing the same, and secondary battery and method for producing the same
KR1020210043712A
